Phosphorus-based negative electrode material with coating structure and preparation method and application thereof
通过在磷基负极材料上包覆纳米纤维材料、吡咯和5-氮杂吲哚的包覆层,并利用纳米磷化镍、红磷和碳纳米球的组合,解决了磷基负极材料在充放电循环过程中体积膨胀率大和粘附性不足的问题,显著提高了材料的循环稳定性和电化学性能。
Patent Information
- Application Number
- CN202411853949.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The existing phosphorus-based negative electrode materials have a large volume expansion rate during the charge and discharge cycle, and insufficient adhesion and stability, resulting in poor circulation performance.
The main phosphorus-based material is prepared by nano nickel phosphide, red phosphorus and carbon nanosphere ball mills, and the surface is coated with nanofiber material, pyrrole and 5-azaiindole as components to enhance the stability and electrochemical properties of the material.
Through the design of the cladding layer, the volume expansion rate of the phosphorus negative electrode material is reduced, the interface effect with the binder is enhanced, and the cyclic stability and ionic conductivity of the electrode are improved.
Smart Images

Figure BDA0005191298250000141 
Figure BDA0005191298250000151 
Figure BDA0005191298250000152
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a phosphorus-based negative electrode material with a coating structure and a preparation method and application thereof. Background Art
[0002] The negative electrode is the key factor that restricts the change of battery rate characteristics. As a negative electrode material, graphite has a low theoretical capacity (372mAh / g) that can no longer meet the increasing demand for battery energy density. As a new type of negative electrode material, phosphorus has a higher theoretical capacity (2596mAh / g) and a lower window voltage. At present, the commonly used phosphorus isomorphs of phosphorus-based negative electrode materials are red phosphorus and black phosphorus, but at present. Red phosphorus is cheap and easy to obtain, but the inner electron conductivity is low. Black phosphorus has relatively high stability and conductivity, but it is difficult to prepare. Both red phosphorus and black phosphorus have excessive volume expansion rates during the charge and discharge cycle, and nano-scale phosphorus is easily oxidized in the air to form an insulating passivation layer, resulting in reduced electrochemical activity. Therefore, phosphorus alone as a negative electrode material has extremely poor cycle performance. In order to improve the stability of phosphorus-based negative electrode materials, existing research tends to use phosphorus-carbon materials in combination to improve the performance of phosphorus-based negative electrode materials.
[0003] The Chinese invention patent with publication number CN112420999B discloses a phosphorus-based negative electrode material with a coating structure for lithium / sodium / potassium ion batteries. The negative electrode material comprises: a core body and a coating layer coated on the outer surface of the core body; wherein the core body is composed of a phosphorus-based material, and the coating layer material is M a X b Or carbon-based materials. This phosphorus-based negative electrode material can not only inhibit the dissolution of lithium phosphide, a product of the cycle process, but also inhibit the side reaction between the electrode interface and the electrolyte, thereby improving the cycle life of the battery. However, the existing technology has technical problems such as large volume expansion rate of phosphorus-based negative electrode materials and insufficient adhesion and stability after being applied to the negative electrode of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a phosphorus-based negative electrode material with a coating structure and a preparation method and application thereof, so as to solve the technical problems in the prior art that the phosphorus-based negative electrode material has a large volume expansion rate and insufficient adhesion and stability after being applied to the battery negative electrode.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A phosphorus-based negative electrode material with a coating structure, comprising a coating layer and a main phosphorus-based material from outside to inside;
[0007] The coating layer is prepared from the following components in parts by weight: 5 to 8 parts of nanofiber material, 5 to 10 parts of pyrrole and 1 to 5 parts of 5-azaindole;
[0008] The main phosphorus-based material is prepared from the following components by weight: 1 to 5 parts of nano nickel phosphide, 5 to 15 parts of red phosphorus and 3 to 8 parts of carbon nanospheres;
[0009] The fiber material is one or more combinations of sulfonated cellulose, bacterial cellulose and algae cellulose, and the cellulose length is 20 to 50 μm;
[0010] The mass of the coating layer accounts for 10 to 30% of the total mass of the phosphorus-based negative electrode material;
[0011] The red phosphorus is commercial red phosphorus, which needs to be pre-processed by ball milling for 20 to 24 hours before use until the average particle size of the red phosphorus is 1 to 2 μm;
[0012] The carbon nanospheres have an average particle size of 200-300 nm, an internal hollow diameter of 80-100 nm, a pore size of 2-5 nm, and a specific surface area of 450-500 m 2 / g.
[0013] A method for preparing a phosphorus-based negative electrode material with a coating structure comprises the following steps:
[0014] S1, adding the main phosphorus-based material, the nanofiber material, pyrrole and 5-azaindole into deionized water, and ultrasonically treating for 1 to 5 minutes to obtain a mixed solution;
[0015] S2. Add a coagulant dropwise to the mixed solution within 20 to 30 minutes, react at 0 to 5°C for 12 to 16 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
[0016] Preferably, the amount of deionized water added to S1 is 150-300 parts by weight; the coagulant in S2 is 10-15wt% ferric chloride solution, and the amount added is 10-15 parts.
[0017] The preparation method of the main phosphorus-based material comprises the following steps:
[0018] S11, drying the carbon nanospheres in an argon atmosphere at 700-800° C. for 1-2 h to remove impurities as a pretreatment;
[0019] S12, adding anhydrous nickel chloride and black phosphorene dispersion into a reaction kettle under the condition of passing argon gas, reacting at 100-150° C. for 4-6 hours, filtering and vacuum drying to obtain nano nickel phosphide, and storing in an argon atmosphere for later use;
[0020] S13. Add nano nickel phosphide, red phosphorus and carbon nanospheres into a high energy ball mill, and mill for 12 to 24 hours under the condition of passing argon gas to obtain a main phosphorus-based material.
[0021] Preferably, the concentration of the black phosphorene dispersion in S12 is 0.5-1 mg / mL, the average particle size of the black phosphorene is 100-200 nm, and the thickness is 1-5 layers.
[0022] Preferably, the mass ratio of anhydrous nickel chloride to black phosphorene in S12 is 1.5 to 2:1.
[0023] The present invention also provides an application of a phosphorus-based negative electrode material with a coating structure, which is used to prepare a battery negative electrode. The preparation method comprises the following steps:
[0024] S21, adding a phosphorus-based negative electrode material having a coating structure, a conductive agent and a binder into an organic solvent, and stirring to form a slurry;
[0025] S22, coating the slurry on the copper foil, compacting it by a tablet press, controlling the coating layer thickness to be between 50 and 150 μm, and punching and cutting to obtain the coated copper foil;
[0026] S23, vacuum drying the coated copper foil at 60-70° C. to obtain a negative electrode plate of the battery.
[0027] Preferably, the conductive agent in S21 is one or more combinations of conductive graphite, acetylene black and Ketjen black.
[0028] Preferably, the organic solvent in S21 is one or more combinations of N-methylpyrrolidone, n-heptane, n-hexane and tetrahydrofuran.
[0029] Preferably, the mass parts of the substances in S21 are 6 to 8 parts of phosphorus-based negative electrode material with a coating structure, 1 to 3 parts of conductive agent and 0.5 to 1.5 parts of binder.
[0030] Preferably, the method for preparing the binder comprises the following steps:
[0031] S31, dissolving chitosan in acetic acid, ultrasonically dispersing for 5 to 10 minutes, and stirring at room temperature for 6 to 12 hours;
[0032] S32, add 5-hydroxyvanillin under stirring, stir for 1-2 hours, add 10-15 wt% sodium borate solution dropwise at 0-5°C until a white solid precipitates, and collect the white solid by filtration;
[0033] S33. Wash the white solid with deionized water, add it to a dialysis bag and dialyze it for 5 to 6 hours. The dialysate is 0.5 to 1 wt% hydrochloric acid. Collect the precipitate, purify it with acetic acid for 2 to 3 hours, and freeze-dry it for 1 to 2 days to obtain a binder.
[0034] Preferably, the mass parts of each substance in S31 and S32 are 1 to 3 parts of chitosan, 50 to 80 parts of acetic acid and 1 to 3 parts of 5-hydroxyvanillin respectively.
[0035] Preferably, the acetic acid concentration in S31 is 1-3wt%, and the acetic acid concentration in S33 is 0.5-1wt%.
[0036] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0037] 1. Based on the prior art, the present invention prepares a main phosphorus-based material by ball milling nano nickel phosphide, red phosphorus and carbon nanospheres, and then coats the main phosphorus-based material with a coating layer prepared by nano fiber material, pyrrole and 5-azaindole, so that the phosphorus-based negative electrode material coating layer has elasticity, reduces the volume expansion rate of the phosphorus negative electrode material, and enhances the interface effect between the phosphorus-based negative electrode material and the binder. The phosphorus-loaded carbon nanospheres can not only provide an effective diffusion channel for electron and ion transmission, but also effectively alleviate the volume expansion of the phosphorus negative electrode material, thereby improving the cycle stability and ionic conductivity of the electrode.
[0038] 2. The present invention grows and prepares nickel phosphide on black phosphorus nanosheets, so that the nickel phosphide has good dispersibility and can effectively prevent the agglomeration of nickel phosphide nanocrystals, thereby improving the energy storage capacity of nickel phosphide. Nickel phosphide and red phosphorus can form a covalent heterostructure. Nickel phosphide serves as a mechanical support to prevent the agglomeration and pulverization of red phosphorus particles during the charge and discharge process, thereby solving the volume expansion problem of phosphorus negative electrode materials.
[0039] 3. The present invention uses nanofiber material as the coating layer substrate, and adsorbs polypyrrole and 5-azaindole formed by oxidative polymerization of pyrrole through hydrogen bonds, so that the coating layer has more active sites, thereby improving the energy storage capacity of the phosphorus negative electrode material, and the coating layer has strong flexibility, and the phosphorus negative electrode material expands and shrinks.
[0040] 4. The binder prepared by grafting 5-hydroxyvanillin with chitosan in the present invention has an amine group with strong chemical adsorption capacity for phosphorus negative electrode materials, a benzene ring with a hydrophobic structure, and a phenolic hydroxyl group with a hydrophilic structure. Therefore, after grafting 5-hydroxyvanillin, the binder has excellent anti-wet adhesion performance and can prevent the dissolution of phosphorus elements to improve the electrode cycle efficiency. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Embodiment 1, a phosphorus-based negative electrode material with a coating structure of this embodiment comprises a coating layer and a main phosphorus-based material;
[0043] The coating layer is prepared from the following components in parts by mass: 3 parts of nanofiber material, 5 parts of pyrrole and 2 parts of 5-azaindole;
[0044] The main phosphorus-based material is prepared from the following components by weight: 2 parts of nano nickel phosphide, 10 parts of red phosphorus and 5 parts of carbon nanospheres;
[0045] The fiber material is sulfonated cellulose, and the cellulose length is 30 μm;
[0046] The mass of the coating layer accounts for 15% of the total mass of the phosphorus-based negative electrode material;
[0047] The red phosphorus is commercial red phosphorus, which needs to be ball-milled for 24 hours before use until the average particle size of the red phosphorus is 1 μm;
[0048] The carbon nanospheres have an average particle size of 300 nm, an internal hollow diameter of 100 nm, a pore size of 5 nm, and a specific surface area of 450 m 2 / g.
[0049] A method for preparing a phosphorus-based negative electrode material with a coating structure comprises the following steps:
[0050] S1, adding 14 parts of the main phosphorus-based material, 3 parts of sulfonated cellulose, 5 parts of pyrrole and 2 parts of 5-azaindole into 200 parts of deionized water, and ultrasonically treating for 1 min to obtain a mixed solution;
[0051] S2. Add 10 parts of 15 wt% ferric chloride solution to the mixed solution within 30 minutes, react at 0°C for 16 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
[0052] The preparation method of the main phosphorus-based material comprises the following steps:
[0053] S11, drying the carbon nanospheres in an argon atmosphere at 800° C. for 2 h to remove impurities as a pretreatment;
[0054] S12, under the condition of passing argon gas, 0.2 parts of anhydrous nickel chloride and 100 parts of a black phosphorene dispersion with a concentration of 1 mg / mL, an average particle size of black phosphorene of 105 nm, and a thickness of 1 layer are added into a reaction kettle, reacted at 120° C. for 5 h, filtered and vacuum dried to obtain nano nickel phosphide, and stored in an argon atmosphere for later use;
[0055] S13. Add 2 parts of nano nickel phosphide, 10 parts of red phosphorus and 5 parts of carbon nanospheres into a high energy ball mill, and ball mill for 24 hours under the condition of passing argon gas to obtain the main phosphorus-based material.
[0056] An application of a phosphorus-based negative electrode material with a coating structure in this embodiment is used to prepare a negative electrode for a battery, and the preparation method includes the following steps:
[0057] S21, adding 7 parts of phosphorus-based negative electrode material with a coating structure, 2 parts of conductive graphite and 1 part of a binder into N-methylpyrrolidone, and stirring evenly to prepare a slurry with a solid content of 75 wt%;
[0058] S22, coating the slurry on a copper foil, compacting it with a tablet press, controlling the coating layer thickness to be 100 μm, and punching and cutting to obtain a coated copper foil;
[0059] S23, vacuum drying the coated copper foil at 60°C to obtain a negative electrode plate of the battery.
[0060] The preparation method of the binder of this embodiment comprises the following steps:
[0061] S31, dissolving 2 parts of chitosan in 100 parts of 1 wt% acetic acid, ultrasonically dispersing for 10 min, and stirring at room temperature for 10 h;
[0062] S32, add 1.5 parts of 5-hydroxyvanillin under stirring, stir for 2 hours, add 15 wt% sodium borate solution dropwise at 0°C until a white solid precipitates, and collect the white solid by filtration;
[0063] S33. Wash the white solid with deionized water, add it into a dialysis bag and dialyze it for 6 hours. The dialysate is 0.5wt% hydrochloric acid. Collect the precipitate, purify it with 0.5wt% acetic acid for 2 hours, and freeze-dry it for 1 day to obtain a binder.
[0064] Embodiment 2, a phosphorus-based negative electrode material with a coating structure of this embodiment, comprising a coating layer and a main phosphorus-based material;
[0065] The coating layer is prepared from the following components in parts by mass: 2 parts of nanofiber material, 6 parts of pyrrole and 1 part of 5-azaindole;
[0066] The main phosphorus-based material is prepared from the following components by weight: 4 parts of nano nickel phosphide, 8 parts of red phosphorus and 3 parts of carbon nanospheres;
[0067] The fiber material is bacterial cellulose, and the cellulose length is 20 μm;
[0068] The mass of the coating layer accounts for 20% of the total mass of the phosphorus-based negative electrode material;
[0069] The red phosphorus is commercial red phosphorus, which needs to be ball-milled for 24 hours before use until the average particle size of the red phosphorus is 2 μm;
[0070] The carbon nanospheres have an average particle size of 250 nm, an internal hollow diameter of 90 nm, a pore size of 3 nm, and a specific surface area of 480 m 2 / g.
[0071] A method for preparing a phosphorus-based negative electrode material with a coating structure comprises the following steps:
[0072] S1, adding 15 parts of the main phosphorus-based material, 2 parts of bacterial cellulose, 6 parts of pyrrole and 1 part of 5-azaindole to 150 parts of deionized water, and ultrasonically treating for 1 min to obtain a mixed solution;
[0073] S2. Add 10 parts of 10 wt% ferric chloride solution to the mixed solution within 20 minutes, react at 1°C for 12 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
[0074] The preparation method of the main phosphorus-based material comprises the following steps:
[0075] S11, drying the carbon nanospheres in an argon atmosphere at 750° C. for 2 h to remove impurities as a pretreatment;
[0076] S12, under the condition of passing argon gas, 0.2 parts of anhydrous nickel chloride and 100 parts of a black phosphorene dispersion with a concentration of 1 mg / mL, an average particle size of black phosphorene of 134 nm, and a thickness of 2 layers are added into a reaction kettle, reacted at 100° C. for 6 hours, filtered and vacuum dried to obtain nano nickel phosphide, and stored in an argon atmosphere for later use;
[0077] S13. Add 4 parts of nano nickel phosphide, 8 parts of red phosphorus and 3 parts of carbon nanospheres into a high energy ball mill, and mill for 18 hours under the condition of passing argon gas to obtain the main phosphorus-based material.
[0078] An application of a phosphorus-based negative electrode material with a coating structure in this embodiment is used to prepare a negative electrode for a battery, and the preparation method includes the following steps:
[0079] S21, adding 8 parts of phosphorus-based negative electrode material with a coating structure, 1.5 parts of acetylene black and 0.5 parts of a binder into tetrahydrofuran, and stirring evenly to prepare a slurry with a solid content of 70 wt%;
[0080] S22, coating the slurry on a copper foil, compacting it through a tablet press, controlling the coating layer thickness to be 80 μm, and punching and cutting to obtain a coated copper foil;
[0081] S23, vacuum drying the coated copper foil at 60°C to obtain a negative electrode plate of the battery.
[0082] The preparation method of the binder of this embodiment comprises the following steps:
[0083] S31, dissolving 2 parts of chitosan in 100 parts of 1 wt% acetic acid, ultrasonically dispersing for 10 min, and stirring at room temperature for 10 h;
[0084] S32, add 1 part of 5-hydroxyvanillin under stirring, stir for 2 hours, add 15 wt% sodium borate solution dropwise at 0°C until a white solid precipitates, and collect the white solid by filtration;
[0085] S33. Wash the white solid with deionized water, add it into a dialysis bag and dialyze it for 6 hours. The dialysate is 0.5wt% hydrochloric acid. Collect the precipitate, purify it with 0.5wt% acetic acid for 3 hours, and freeze-dry it for 1 day to obtain the binder.
[0086] Embodiment 3, a phosphorus-based negative electrode material with a coating structure of this embodiment comprises a coating layer and a main phosphorus-based material;
[0087] The coating layer is prepared from the following components in parts by mass: 4 parts of nanofiber material, 9 parts of pyrrole and 1 part of 5-azaindole;
[0088] The main phosphorus-based material is prepared from the following components by weight: 1.5 parts of nano nickel phosphide, 8 parts of red phosphorus and 6.5 parts of carbon nanospheres;
[0089] The fiber material is algae cellulose, and the cellulose length is 45 μm;
[0090] The mass of the coating layer accounts for 26.5% of the total mass of the phosphorus-based negative electrode material;
[0091] The red phosphorus is commercial red phosphorus, which needs to be ball-milled for 24 hours before use until the average particle size of the red phosphorus is 1.5 μm;
[0092] The carbon nanospheres have an average particle size of 240 nm, an internal hollow diameter of 81 nm, a pore size of 3.5 nm, and a specific surface area of 460 m 2 / g.
[0093] A method for preparing a phosphorus-based negative electrode material with a coating structure comprises the following steps:
[0094] S1, adding 15 parts of the main phosphorus-based material, 4 parts of algae cellulose, 9 parts of pyrrole and 1 part of 5-azaindole into 200 parts of deionized water, and ultrasonically treating for 3 minutes to obtain a mixed solution;
[0095] S2. Add 12 parts of 11 wt% ferric chloride solution to the mixed solution within 30 minutes, react at 4°C for 16 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
[0096] The preparation method of the main phosphorus-based material comprises the following steps:
[0097] S11, drying the carbon nanospheres in an argon atmosphere at 700° C. for 2 h to remove impurities as a pretreatment;
[0098] S12, under the condition of passing argon gas, 0.1 parts of anhydrous nickel chloride and 100 parts of a black phosphorene dispersion with a concentration of 0.5 mg / mL, an average particle size of black phosphorene of 121 nm, and a thickness of 1 layer are added into a reaction kettle, reacted at 120° C. for 5 h, filtered and vacuum dried to obtain nano nickel phosphide, and stored in an argon atmosphere for later use;
[0099] S13. Add 2 parts of nano nickel phosphide, 10 parts of red phosphorus and 5 parts of carbon nanospheres into a high energy ball mill, and ball mill for 24 hours under the condition of passing argon gas to obtain the main phosphorus-based material.
[0100] An application of a phosphorus-based negative electrode material with a coating structure in this embodiment is used to prepare a negative electrode for a battery, and the preparation method includes the following steps:
[0101] S21, adding 7.5 parts of a phosphorus-based negative electrode material having a coating structure, 1.5 parts of Ketjen black and 1 part of a binder into N-methylpyrrolidone, and stirring evenly to prepare a slurry having a solid content of 80 wt%;
[0102] S22, coating the slurry on a copper foil, compacting it with a tablet press, controlling the coating layer thickness to be 100 μm, and punching and cutting to obtain a coated copper foil;
[0103] S23, vacuum drying the coated copper foil at 65°C to obtain a negative electrode plate of the battery.
[0104] The preparation method of the binder of this embodiment comprises the following steps:
[0105] S31, dissolving 2 parts of chitosan in 100 parts of 2 wt% acetic acid, ultrasonically dispersing for 10 min, and stirring at room temperature for 12 h;
[0106] S32, add 1.5 parts of 5-hydroxyvanillin under stirring, stir for 2 hours, add 15 wt% sodium borate solution dropwise at 0°C until a white solid precipitates, and collect the white solid by filtration;
[0107] S33. Wash the white solid with deionized water, add it into a dialysis bag and dialyze it for 6 hours. The dialysate is 0.8 wt% hydrochloric acid. Collect the precipitate, purify it with 0.8 wt% acetic acid for 3 hours, and freeze-dry it for 2 days to obtain a binder.
[0108] Embodiment 4, a phosphorus-based negative electrode material with a coating structure of this embodiment comprises a coating layer and a main phosphorus-based material;
[0109] The coating layer is prepared from the following components in parts by mass: 3 parts of nanofiber material, 9 parts of pyrrole and 3 parts of 5-azaindole;
[0110] The main phosphorus-based material is prepared from the following components by weight: 4 parts of nano nickel phosphide, 15 parts of red phosphorus and 8 parts of carbon nanospheres;
[0111] The fiber material is a mixture of sulfonated cellulose and algae cellulose in a mass ratio of 1:1, and the cellulose length is 35 μm;
[0112] The mass of the coating layer accounts for 12.5% of the total mass of the phosphorus-based negative electrode material;
[0113] The red phosphorus is commercial red phosphorus, which needs to be ball-milled for 20 hours before use until the average particle size of the red phosphorus is 1 μm;
[0114] The carbon nanospheres have an average particle size of 200 nm, an internal hollow diameter of 80 nm, a pore size of 2 nm, and a specific surface area of 455 m 2 / g.
[0115] A method for preparing a phosphorus-based negative electrode material with a coating structure comprises the following steps:
[0116] S1, adding 27 parts of the main phosphorus-based material, 1.5 parts of sulfonated cellulose, 1.5 parts of algae cellulose, 9 parts of pyrrole and 3 parts of 5-azaindole into 300 parts of deionized water, and ultrasonically treating for 5 minutes to obtain a mixed solution;
[0117] S2. Add 15 parts of 15 wt% ferric chloride solution to the mixed solution within 30 minutes, react at 0°C for 16 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
[0118] The preparation method of the main phosphorus-based material comprises the following steps:
[0119] S11, drying the carbon nanospheres in an argon atmosphere at 800° C. for 1 h to remove impurities as a pretreatment;
[0120] S12, under the condition of passing argon gas, 0.2 parts of anhydrous nickel chloride and 100 parts of a black phosphorene dispersion with a concentration of 1 mg / mL, an average particle size of black phosphorene of 191 nm, and a thickness of 5 layers are added into a reaction kettle, reacted at 150° C. for 6 hours, filtered and vacuum dried to obtain nano nickel phosphide, and stored in an argon atmosphere for later use;
[0121] S13. Add 2 parts of nano nickel phosphide, 10 parts of red phosphorus and 5 parts of carbon nanospheres into a high energy ball mill, and ball mill for 24 hours under the condition of passing argon gas to obtain the main phosphorus-based material.
[0122] An application of a phosphorus-based negative electrode material with a coating structure in this embodiment is used to prepare a negative electrode for a battery, and the preparation method includes the following steps:
[0123] S21, adding 7 parts of phosphorus-based negative electrode material with a coating structure, 2 parts of a conductive agent and 1 part of a binder into N-methylpyrrolidone, and stirring evenly to prepare a slurry with a solid content of 75 wt%;
[0124] S22, coating the slurry on a copper foil, compacting it with a tablet press, controlling the coating layer thickness to be 100 μm, and punching and cutting to obtain a coated copper foil;
[0125] S23, vacuum drying the coated copper foil at 60°C to obtain a negative electrode plate of the battery.
[0126] The preparation method of the binder of this embodiment comprises the following steps:
[0127] S31, dissolving 1 part of chitosan in 50 parts of 2 wt% acetic acid, ultrasonically dispersing for 5 min, and stirring at room temperature for 10 h;
[0128] S32, add 1 part of 5-hydroxyvanillin under stirring, stir for 2 hours, add 10 wt % sodium borate solution dropwise at 0° C. until a white solid precipitates, and collect the white solid by filtration;
[0129] S33. Wash the white solid with deionized water, add it into a dialysis bag and dialyze it for 6 hours. The dialysate is 0.5wt% hydrochloric acid. Collect the precipitate, purify it with 0.5wt% acetic acid for 2 hours, and freeze-dry it for 1.5 days to obtain a binder.
[0130] Embodiment 5, a phosphorus-based negative electrode material with a coating structure of this embodiment comprises a coating layer and a main phosphorus-based material;
[0131] The coating layer is prepared from the following components in parts by mass: 4 parts of nanofiber material, 5 parts of pyrrole and 1 part of 5-azaindole;
[0132] The main phosphorus-based material is prepared from the following components by weight: 1 part of nano nickel phosphide, 5 parts of red phosphorus and 3 parts of carbon nanospheres;
[0133] The fiber material is a mixture of bacterial cellulose and algae cellulose in a mass ratio of 3:1, and the cellulose length is 25 μm;
[0134] The mass of the coating layer accounts for 30% of the total mass of the phosphorus-based negative electrode material;
[0135] The red phosphorus is commercial red phosphorus, which needs to be ball-milled for 20 hours before use until the average particle size of the red phosphorus is 1 to 2 μm;
[0136] The carbon nanospheres have an average particle size of 300 nm, an internal hollow diameter of 100 nm, a pore size of 5 nm, and a specific surface area of 450 m 2 / g.
[0137] A method for preparing a phosphorus-based negative electrode material with a coating structure comprises the following steps:
[0138] S1, adding 9 parts of the main phosphorus-based material, 3 parts of bacterial cellulose, 1 part of algae cellulose, 5 parts of pyrrole and 1 part of 5-azaindole to 150 parts of deionized water, and ultrasonically treating for 1 min to obtain a mixed solution;
[0139] S2. Add 15 parts of 10 wt% ferric chloride solution to the mixed solution within 30 minutes, react at 0°C for 12 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
[0140] The preparation method of the main phosphorus-based material comprises the following steps:
[0141] S11, drying the carbon nanospheres in an argon atmosphere at 800° C. for 2 h to remove impurities as a pretreatment;
[0142] S12, under the condition of passing argon gas, 0.2 parts of anhydrous nickel chloride and 100 parts of a black phosphorene dispersion with a concentration of 1 mg / mL, an average particle size of black phosphorene of 105 nm, and a thickness of 1 layer are added into a reaction kettle, reacted at 120° C. for 5 h, filtered and vacuum dried to obtain nano nickel phosphide, and stored in an argon atmosphere for later use;
[0143] S13. Add 1 part of nano nickel phosphide, 5 parts of red phosphorus and 3 parts of carbon nanospheres into a high energy ball mill, and ball mill for 24 hours under the condition of passing argon gas to obtain the main phosphorus-based material.
[0144] An application of a phosphorus-based negative electrode material with a coating structure in this embodiment is used to prepare a negative electrode for a battery, and the preparation method includes the following steps:
[0145] S21, adding 6 parts of phosphorus-based negative electrode material with a coating structure, 1 part of acetylene black, 1 part of conductive graphite and 1 part of a binder into n-hexane, and stirring evenly to prepare a slurry with a solid content of 80 wt%;
[0146] S22, coating the slurry on a copper foil, compacting it with a tablet press, controlling the coating layer thickness to be 150 μm, and punching and cutting to obtain a coated copper foil;
[0147] S23, vacuum drying the coated copper foil at 70° C. to obtain a negative electrode plate of the battery.
[0148] The preparation method of the binder of this embodiment comprises the following steps:
[0149] S31, dissolving 1 part of chitosan in 50 parts of 2 wt% acetic acid, ultrasonically dispersing for 5 min, and stirring at room temperature for 10 h;
[0150] S32, add 0.9 parts of 5-hydroxyvanillin under stirring, stir for 2 hours, add 10 wt% sodium borate solution dropwise at 0°C until a white solid precipitates, and collect the white solid by filtration;
[0151] S33. Wash the white solid with deionized water, add it into a dialysis bag and dialyze it for 6 hours. The dialysate is 0.5wt% hydrochloric acid. Collect the precipitate, purify it with 0.5wt% acetic acid for 2.5 hours, and freeze-dry it for 1.5 days to obtain a binder.
[0152] Comparative Example 1: This comparative example differs from Example 1 in that the nickel phosphide is prepared by hydrothermal reaction of nickel nitrate hexahydrate and red phosphorus.
[0153] Comparative Example 2: The difference between this comparative example and Example 1 is that the material used for the coating layer is changed to polyaniline.
[0154] Comparative Example 3: The difference between this comparative example and Example 1 is that the binder used in the phosphorus-based negative electrode material for preparing the battery negative electrode is changed to polyvinylidene fluoride.
[0155] Performance Testing
[0156] Battery preparation: A battery was prepared by assembling a lithium iron phosphate electrode sheet as the positive electrode sheet, 1 mol / L lithium hexafluorophosphate (ethylene carbonate and diethyl carbonate mixed in equal volumes as the solvent) as the electrolyte, a glass fiber membrane as the battery separator, and the negative electrode sheets prepared in each embodiment and comparative example.
[0157] The test batteries prepared in each embodiment and comparative example were tested by commercially available testing equipment to test the first week discharge capacity, capacity retention rate after 200 cycles and cycle life. The test results are shown in Table 1 below:
[0158] Table 1
[0159]
[0160]
[0161] According to the data in Table 1, the first-week discharge specific capacity of the test batteries of Examples 1 to 5 is between 1764 and 1855 mAh / g, and the capacity retention rate after 200 cycles is above 86.5%, indicating that the negative electrode of the test battery has a good discharge specific capacity and reduces the loss of battery cycle discharge capacity; the cycle life of the test battery of Examples 1 to 5 is 550 times, indicating that the test battery has a long service life, further illustrating that the phosphorus-based negative electrode material prepared by the present invention has high ionic conductivity and cycle stability.
[0162] Peel strength test
[0163] According to GB / T 2792-2014 "Test method for peel strength of adhesive tape", the peel strength of the negative electrode sheets prepared in each embodiment and comparative example was measured. The test results are shown in Table 2 below:
[0164] Table 2
[0165]
[0166]
[0167] According to the data in Table 1, the peel strength of the negative electrode sheets prepared in Examples 1 to 5 is between 5.4 and 6.1 N / cm. The peel strength of the negative electrode prepared in Comparative Example 3 is 3.3 N / cm after the binder is changed to polyvinylidene fluoride, indicating that the mechanical properties of the electrode sheet are improved after the phosphorus-based negative electrode material and binder prepared in the present invention are used to prepare the negative electrode sheet.
[0168] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0169] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A phosphorus-based negative electrode material having a coating structure, characterized in that: It includes a coating layer and a main phosphorus-based material from outside to inside; The coating layer is prepared from the following components in parts by weight: 1 to 5 parts of nanofiber material, 5 to 10 parts of pyrrole and 1 to 5 parts of 5-azaindole; The main phosphorus-based material is prepared from the following components by weight: 1 to 5 parts of nano nickel phosphide, 5 to 15 parts of red phosphorus and 3 to 8 parts of carbon nanospheres; The mass of the coating layer accounts for 10-30% of the total mass of the phosphorus-based negative electrode material.
2. The phosphorus-based negative electrode material with a coating structure according to claim 1, characterized in that: The red phosphorus needs to be pre-processed by ball milling for 20 to 24 hours before use to a particle size of 1 to 2 μm; The carbon nanospheres have an average particle size of 200-300 nm, an internal hollow diameter of 80-100 nm, a pore size of 2-5 nm, and a specific surface area of 450-500 m 2 / g; The nanofiber material is one or more combinations of sulfonated cellulose, bacterial cellulose, and algae cellulose, and the length of the cellulose is 20 to 50 μm.
3. A method for preparing a phosphorus-based negative electrode material having a coating structure, characterized in that: The steps include: S1, adding the main phosphorus-based material, the nanofiber material, pyrrole and 5-azaindole into deionized water, and ultrasonically treating for 1 to 5 minutes to obtain a mixed solution; S2. Add a coagulant dropwise to the mixed solution within 20 to 30 minutes, react at 0 to 5°C for 12 to 16 hours, collect the solid by filtration, wash with deionized water, and dry to obtain a phosphorus-based negative electrode material with a coated structure.
4. The method for preparing a phosphorus-based negative electrode material with a coating structure according to claim 3, characterized in that: In terms of parts by mass, the amount of deionized water added in S1 is 150 to 300 parts; the coagulant in S2 is a 10 to 15 wt % ferric chloride solution, and the amount of deionized water added is 10 to 15 parts.
5. The method for preparing a phosphorus-based negative electrode material with a coating structure according to claim 3, characterized in that: The preparation method of the main phosphorus-based material comprises the following steps: S11, drying the carbon nanospheres in an argon atmosphere at 700-800° C. for 1-2 h to remove impurities as a pretreatment; S12, adding anhydrous nickel chloride and black phosphorene dispersion into a reaction kettle under the condition of passing argon gas, reacting at 100-150° C. for 4-6 hours, filtering and vacuum drying to obtain nano nickel phosphide, and storing in an argon atmosphere for later use; S13. Add nano nickel phosphide, red phosphorus and carbon nanospheres into a high energy ball mill, and mill for 12 to 24 hours under the condition of passing argon gas to obtain a main phosphorus-based material.
6. The method for preparing a phosphorus-based negative electrode material with a coating structure according to claim 5, characterized in that: The concentration of the black phosphorene dispersion in the S12 is 0.5-1 mg / mL, the average particle size of the black phosphorene is 100-200 nm, the thickness is 1-5 layers, and the mass ratio of anhydrous nickel chloride to black phosphorene is 1.5-2:
1.
7. Application of phosphorus-based negative electrode materials with a coating structure, characterized in that: The method is applied to prepare a negative electrode of a battery, and the preparation method comprises the following steps: S21, adding a phosphorus-based negative electrode material having a coating structure, a conductive agent and a binder into an organic solvent, and stirring to form a slurry; S22, coating the slurry on the copper foil, compacting it by a tablet press, controlling the coating layer thickness to be between 50 and 150 μm, and punching and cutting to obtain the coated copper foil; S23, vacuum drying the coated copper foil at 60-70° C. to obtain a negative electrode plate of the battery.
8. The use of the phosphorus-based negative electrode material with a coating structure according to claim 7, characterized in that: The conductive agent in S21 is one or more combinations of conductive graphite, acetylene black and Ketjen black, the organic solvent is one or more combinations of N-methylpyrrolidone, n-heptane, n-hexane and tetrahydrofuran, and the mass parts of each substance used are 6 to 8 parts of phosphorus-based negative electrode material with a coated structure, 1 to 3 parts of conductive agent and 0.5 to 1.5 parts of binder.
9. The use of the phosphorus-based negative electrode material with a coating structure according to claim 7, characterized in that: The preparation method of the binder comprises the following steps: S31, dissolving chitosan in acetic acid, ultrasonically dispersing for 5 to 10 minutes, and stirring at room temperature for 6 to 12 hours; S32, add 5-hydroxyvanillin under stirring, stir for 1-2 hours, add 10-15 wt% sodium borate solution dropwise at 0-5°C until a white solid precipitates, and collect the white solid by filtration; S33. Wash the white solid with deionized water, add it to a dialysis bag and dialyze it for 5 to 6 hours. The dialysate is 0.5 to 1 wt% hydrochloric acid. Collect the precipitate, purify it with acetic acid for 2 to 3 hours, and freeze-dry it for 1 to 2 days to obtain a binder.
10. The use of a phosphorus-based negative electrode material with a coating structure according to claim 9, characterized in that: The mass parts of each substance used in S31 and S32 are 1-3 parts of chitosan, 50-80 parts of acetic acid and 1-3 parts of 5-hydroxyvanillin respectively. The acetic acid concentration of S31 is 1-3wt%, and the acetic acid concentration of S33 is 0.5-1wt%.
Citation Information
Patent Citations
Phosphorus-based anode materials with coating structure, their preparation methods and applications
CN112420999B
Cited By
Preparation method and application of NiP3 / FeP4 heterojunction carbon composite material
CN120757108A